Immunity of Residual Current Devices to the Impulse Leakage Current in Circuits with Variable Speed Drives - Czapp, S.; Borowski, K. (Elektronika ir Elektrotechnika, 2013)
This paper concerns reliability of supply in variable speed drives circuits with residual current devices. During normal operation of these circuits high value of leakage current causes unwanted tripping of residual current devices. Immunity of residual current devices to the impulse leakage current should be evaluated. The system for testing of residual current devices and results of the test are presented. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.2883